Arabidopsis and Maize RidA Proteins Preempt Reactive Enamine/Imine Damage to Branched-Chain Amino Acid Biosynthesis in Plastids . Issue 7 (28th July 2014) - Niehaus, Thomas D.; Nguyen, Thuy N.D.; Gidda, Satinder K.; ElBadawi-Sidhu, Mona; Lambrecht, Jennifer A.; McCarty, Donald R.; Downs, Diana M.; Cooper, Arthur J.L.; Fiehn, Oliver; Mullen, Robert T.; Hanson, Andrew D.
Abstract : Plant RidA proteins protect an enzyme of branched-chain amino acid biosynthesis from inactivation by hydrolyzing reactive pathway intermediates before they can damage the enzyme. RidA proteins are thus crucial for the efficient biosynthesis of branched-chain amino acids in plants and provide an iconic example of the preemption of metabolite damage. Abstract: RidA (for Reactive Intermediate Deaminase A) proteins are ubiquitous, yet their function in eukaryotes is unclear. It is known that deleting Salmonella enterica ridA causes Ser sensitivity and that S. enterica RidA and its homologs from other organisms hydrolyze the enamine/imine intermediates that Thr dehydratase forms from Ser or Thr. In S. enterica, the Ser-derived enamine/imine inactivates a branched-chain aminotransferase; RidA prevents this damage. Arabidopsis thaliana and maize ( Zea mays ) have a RidA homolog that is predicted to be plastidial. Expression of either homolog complemented the Ser sensitivity of the S. enterica ridA mutant. The purified proteins hydrolyzed the enamines/imines formed by Thr dehydratase from Ser or Thr and protected the Arabidopsis plastidial branched-chain aminotransferase BCAT3 from inactivation by the Ser-derived enamine/imine. In vitro chloroplast import assays and in vivo localization of green fluorescent protein fusions showed that Arabidopsis RidA and Thr dehydratase are chloroplast targeted. Disrupting Arabidopsis RidA reduced root growth and raised the root and shoot levels of the branched-chain amino acid biosynthesis intermediate 2-oxobutanoate; Ser treatment exacerbated these effects in roots. Supplying Ile reversed the root growth defect. These results indicate that plastidial RidA proteins can preempt damage to BCAT3 and Ile biosynthesis by hydrolyzing the Ser-derived enamine/imine product of Thr dehydratase.